2017
DOI: 10.1253/circj.cj-17-0234
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Heart Failure Hospitalization in Patients With Cardiac Resynchronization Therapy With or Without a Defibrillator for Primary Prevention in Japan ― Analysis of the Japan Cardiac Device Treatment Registry Database ―

Abstract: In patients without sustained ventricular tachyarrhythmias enrolled in the JCDTR, there was no significant difference in mortality between the CRT-D and CRT-P groups, despite a lower trend in CRT-D recipients. This study was limited by large clinical and demographic differences between the 2 groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 48 publications
2
19
1
Order By: Relevance
“…They were male gender, younger age, reduced LVEF, and a history of NSVT. In contrast to the COMPANION and REVERSE studies, no significant superiority of CRT‐D to CRT‐P, in terms of reducing the risk of death, was observed in a recent study of the JCDTR after adjusting the clinical variables . This may be in part due to an incomplete adjustment of the study populations.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…They were male gender, younger age, reduced LVEF, and a history of NSVT. In contrast to the COMPANION and REVERSE studies, no significant superiority of CRT‐D to CRT‐P, in terms of reducing the risk of death, was observed in a recent study of the JCDTR after adjusting the clinical variables . This may be in part due to an incomplete adjustment of the study populations.…”
Section: Discussionmentioning
confidence: 78%
“…In Hokkaido University Hospital, the protocol was approved on September 20, 2012, by the Ethics Committee (approval number: 012‐0156). Among 2714 CRT‐D recipients for primary prevention with an implantation date between January 2011 and August 2015, the follow‐up data were available in 620 patients as of September 16, 2015 . Information regarding presence or absence of NSVT had been registered at the CRT‐D implantation in 269 patients (43%).…”
Section: Methodsmentioning
confidence: 99%
“…2,8,9 Several observational studies could not identify symptomatic heart failure patients who benefit more from CTR-D than CRT-P, as there were significant demographic and morbid differences between the two patient groups. 14,18,19 Despite this, the superiority of CRT-D to CRT-P was reported in HFrEF patients with ischemic cardiomyopathy, [20][21][22][23] those with nonischemic cardiomyopathy having left ventricular midwall fibrosis 24 and those with the Goldenberg (MADIT) risk scores 0-2. 25 More recently, CRT-D…”
Section: Discussionmentioning
confidence: 99%
“…First, clinical outcomes are not shown in this study, but we reported several outcomes in other studies. 19,30 Second, the rate of registration with the JCDTR is decreasing as evident from the data of JADIA. For example, ratio of registration of the JCDTR to that of JADIA (JCDTR/ JADIA ratio) was 57.0% for ICD and 49.3% for CRT-D in 2011, but it declined gradually.…”
Section: Study Limitationsmentioning
confidence: 95%
“…Patients with HF at high risk of sudden cardiac death (SCD) due to ventricular arrhythmia may be fitted with an implantable cardioverter-defibrillator (ICD) [ 58 ]. Recent guidelines recommend this option in patients with a life expectancy of > 1 year [ 17 , 59 ].…”
Section: End-of-life Care For Patients With Device Therapymentioning
confidence: 99%